What's causing accelerating inflation: Pandemic or policy response? - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2022)
This paper examines the recent increase of the measured inflation rate to assess the degree to which the acceleration is due to problems created (largely on the supply side) by the pandemic versus pressures created on the demand side by pandemic relief. Some have attributed the inflation to excess demand, most notably Larry Summers, who had warned that the pandemic relief spending was too great. As evidence, one could point to the quick recovery of GDP and to reportedly tight labor markets. Others have variously blamed supply chain disruptions, shortages of certain inputs, OPEC's oil price increases, labor market disruptions because of COVID, and rising profit margins obtained through exercise of pricing power. We conclude that there is little evidence that excess demand is the problem, although we agree that in the absence of the relief checks, recovery would have been sufficiently slow to minimize inflation pressure. We closely examine the main contributors to rising overall prices and conclude that tighter monetary policy would not be an effective way to reduce price pressures. We also cast doubt on the expectations theory of inflation control. We present evidence that suggests there is currently little danger that higher inflation will become entrenched. If anything, rate hikes now will make it harder for the economy to adjust to current realities. The potential for lots of pain with little gain is great. The best course of action is to tackle problems on the supply side.
Keywords: E31; E32; E52; E520; 330; COVID-19; Inflation; Pandemic Relief; Pricing Power; Supply Chains